Information Security Awareness in Public Administrations at an International Level - Garayová, Lilla (Public Governance, Administration and Finances Law Review, 2020)
Privacy and data protection laws have changed significantly over the last two decades. The highly networked and interconnected world we live in today was only a flash on the horizon in the 1990s. The Internet itself was still a whole new innovation for many people. Many businesses have not had a public website yet. Concepts, such as online social media platforms, did not exist – and certainly no one thought about how they should be regulated. Smartphones, wearable technology and artificial intelligence have made huge leaps over the past 20 years – powered by new ways of data acquisition and processing. As a result, courts and regulators have increasingly had to adapt the aging data protection laws to suit a constantly changing world for which they were simply not designed. Government digital agendas worldwide go hand in hand with this fast-paced digital evolution. Information security and awareness should be a crucial part of public administration agendas with the primary goal to protect information of all types and origins.